Strategies in Markets for Experience and Credence Goods - Benz, Men-Andri (Markt- und Unternehmensentwicklung Markets and Organisations, 2007)
The quality and characteristics of industrial and consumption goods are often not revealed until after consumption. However, the decision to buy these products must be made before buying. Many strategies and instruments for signalling and screening have been developed in the economic world in order to overcome potential market failure due to insufficient quality detection. In many situations, efficient incentives and quality revelation are given to the market players by contracts that structure the process and payments of the transaction. Additionally, market forces lead to the emergence of new market players as intermediaries. They provide information about the quality of the products by comparing them and reveal credible signs concerning the relative quality valuation of products. Men-Andri Benz develops new pricing and positioning strategies for suppliers of such contracts goods. Using microeconomic tools as contests and incentive contracts, he analyses the basic positioning decisions for contract goods and designs concrete strategies for the specific sectors of sports and religion. The effects on pricing and profits are examined both in general and for each individual industry.